Talent engagement and job satisfaction as the mediators between psychological empowerment and talent outcomes / Shaik Roslinah Bux - Shaik Roslinah, Bux (2012)

(untitled)
This study is an inaugural attempt to examine the incorporation of the psychological aspects of human capital and their relationships with talent engagement, job satisfaction and outcomes of employees. The study is essential as dynamic changes at the workplace have necessitated the engagement and job satisfaction of employees for organizations to achieve global competitiveness (Fay & Luhrmann, 2004). Moreover, in examining the context of talent management, there seemed to be a gap between employees being merely psychologically empowered and talent outcomes. Therefore, this research aims to highlight the importance of talent engagement and investigates how talent engagement and job satisfaction are related with perceived psychological empowerment and talent outcomes through a proposed talent engagement model. The study adopts the concept of psychological empowerment (PE) by Spreitzer (1995) as a possible predictor, and investigates how it is related to two types of talent engagement; namely, job and organization engagement as well as job satisfaction (JS) that would in turn affect two talent outcomes: intention to stay and dedication. Questionnaire was used for the cross-sectional survey to collect primary data. The respondents were the identified talents among participating Kuala Lumpur and Selangor-based GLC from the G-40 list. The G-40 refers to the initial group of 40 GLC in Malaysia. A total of 342 GLC employees through the distributed 400 questionnaires responded to the survey yielding a response rate of 85.5 percent. Analysis was conducted using statistical techniques of SPSS while the hypothesised model was empirically tested using analysis of moment structure (AMOS) of the structural equation modelling (SEM). In ascertaining the model fit, the study also assessed the significance, the direction and the strength of each hypothesised structural parameter. iv The results revealed good internal reliabilities for the six constructs of the study. The results also indicated positive relationships among the six constructs. However, the role of job engagement (JE), organization engagement (OE) and job satisfaction (JS) as mediators was found to be partially supported as there were both direct and indirect effects. Analysis through the significant χ2 difference tests and discriminant analysis showed that the hypothesised six factors partial mediating model had the best overall fit to the data. The research findings provide both theoretical and managerial implications. As there has yet any empirical research that integrates PE with JE and OE to predict the dedication and the intention to stay of employees, this research contributes theoretical value through a proposed talent engagement model. Additionally, the findings also revealed to the transforming GLC on the importance of incorporating talent engagement with PE in their human capital strategy. In essence, it is hoped that the findings in this study and the proposed talent engagement model would facilitate further academic research as well as the development of theories on talent engagement.